2016
DOI: 10.1007/s00467-015-3276-2
|View full text |Cite
|
Sign up to set email alerts
|

The dose–response effect of insulin sensitivity on albuminuria in children according to diabetes type

Abstract: Background Insulin resistance is associated with microalbuminuria among youth with diabetes mellitus. We sought to determine the dose-response effect of insulin sensitivity (IS) on the magnitude of albuminuria and whether there is a threshold below which urine albumin excretion increases. Methods These analyses included participants from the SEARCH for Diabetes in Youth Study with incident diabetes who completed a baseline study visit (N = 2988). We estimated IS using a validated equation incorporating waist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
1
9
1
Order By: Relevance
“…Recently, Zeng et al[94], showed that the ORAI (calcium release-activated calcium channels) are also accountable for the internalization of albumin in proximal tubular epithelial cells via clathrin-mediated endocytosis and expression of these channels is insulin-dependent. In concordance with previous studies, Mottl et al[95] showed that the urinary ACR was positively associated with insulin-resistant young Type 2 diabetic subjects. Moreover, insulin treatment under high-glucose conditions increased megalin expression and albumin internalization in OK cells[96].…”
Section: Renal Ir In Proteinuriasupporting
confidence: 91%
“…Recently, Zeng et al[94], showed that the ORAI (calcium release-activated calcium channels) are also accountable for the internalization of albumin in proximal tubular epithelial cells via clathrin-mediated endocytosis and expression of these channels is insulin-dependent. In concordance with previous studies, Mottl et al[95] showed that the urinary ACR was positively associated with insulin-resistant young Type 2 diabetic subjects. Moreover, insulin treatment under high-glucose conditions increased megalin expression and albumin internalization in OK cells[96].…”
Section: Renal Ir In Proteinuriasupporting
confidence: 91%
“…In a recently published study, SEARCH examined insulin resistance in relation to urinary albumin to creatinine ratio (UACR) in both type 1 and type 2 diabetes. This study indicated that there was an inverse association between insulin resistance and UACR in type 2 diabetes only and that below an insulin sensitivity index of 4.7, the relationship was stronger, suggesting a possible threshold effect [32]. …”
Section: Complications and Comorbiditiesmentioning
confidence: 99%
“…Urine albumin and creatinine were measured as previously described. 21 Blood was processed, and fresh plasma, serum and urine samples were shipped on cold packs by overnight courier to the study central laboratory where analysis of GAD-65 antibodies, insulinoma-associated-2 antibodies, Zinc-T8 autoantibodies, cholesterol, triglycerides and HbA1c was performed as previously described. 22,23 The Bouvet equation was used to calculate estimated glomerular filtration rate (eGFR) at the follow-up visit.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…The insulin sensitivity score was utilized only in analyses of the type 2 diabetes group due to previous work underscoring its strong association in type 2 but not type 1 diabetes. 21,29…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%